Aeromicrobium piscarium sp. nov., isolated from the intestine of Collichthys lucidus. Issue 10 (3rd October 2020) - Zhao, Li-Hua; Xing, Xiang; Liu, Ying-Ying; Sha, Sha; Song, Cui; Sun, Yuan-Hao; Xianyu, Dai-Wei; Zhu, Qian
Abstract : A Gram-stain-positive, rod-shaped, whitesmoke-coloured and aerobic bacterium, designated strain Co35 T, was isolated from the intestine of Collichthys lucidus collected from the Jiangmen Guangdong Chinese White Dolphin Provincial Nature Reserve. Strain Co35 T was able to grow at 15–35 °C (optimal 28 °C), at pH 7.0–8.5 (optimal 8.0) and with 0–9 % (w/v) NaCl (optimal 0.5–1 %). Phylogenetic analysis based on 16S rRNA gene sequences revealed that strain Co35 T was a member of the genus Aeromicrobium within the family Nocardioidaceae . The genomic DNA G+C content of strain Co35 T was 68.4 mol%. Chemotaxonomic analysis showed that the sole respiratory quinone was menaquinone 9 (MK-9), and the major fatty acids included 10-methyl C18 : 0 . The polar lipids were found to consist of phosphatidylglycerol (PG), diphosphatidylglycerol (DPG), phosphatidylethanolamine (PE), phosphatidylinositol (PI), two unidentified phospholipids (PL1–2) and two unidentified glycolipids (GL1–2). On the basis of its phylogenetic, phenotypic, chemotaxonomic, genotypic and genomic characteristics presented in this study, strain Co35 T represents a novel species in the genus Aeromicrobium, for which the name Aeromicrobium piscarium sp. nov. is proposed. The type strain is Co35 T (=KCTC 49280 T =MCCC 1K03754 T ).